2021
DOI: 10.1007/s11130-021-00917-4
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Phenolic Extracts from Cocoa Shells to Enrich Chocolate Bars

Abstract: Cocoa bean shells were subjected to green extraction technologies, based on the absence of toxic organic solvents, to recover polyphenols; the extract was then encapsulated using a spray dryer and maltodextrin as coating agent. The best conditions observed in the spray drying tests (core-to-coating ratio 1:5; inlet temperature 150 °C; flow rate 6 ml min−1) were applied to produce the microcapsules used to enrich the same cocoa mass as the shells and processed for the preparation of the chocolate bars. Sensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Experiments (2, 4, 8, 10, 12, 14, and 15) containing 50 % ethanol had an average of 185 mg GAE/g, 0.15 mmol TE/g, and 0.18 mmol FeSO 4 /g. These results are consistent with Grassia et al [25] , who reported that the highest yield during polyphenol recovery in CBS was with a 50 % v/v ethanolic solution (TPC between 0.80 and 1.20 g/100 g of sample), while in 25 % and 75 % ethanolic solutions, TPC was around 0.40 g/100 g of the sample.…”
Section: Resultssupporting
confidence: 92%
“…Experiments (2, 4, 8, 10, 12, 14, and 15) containing 50 % ethanol had an average of 185 mg GAE/g, 0.15 mmol TE/g, and 0.18 mmol FeSO 4 /g. These results are consistent with Grassia et al [25] , who reported that the highest yield during polyphenol recovery in CBS was with a 50 % v/v ethanolic solution (TPC between 0.80 and 1.20 g/100 g of sample), while in 25 % and 75 % ethanolic solutions, TPC was around 0.40 g/100 g of the sample.…”
Section: Resultssupporting
confidence: 92%
“…There are few studies that use plant materials of various origins to produce functional food products such as chocolate [ 41 , 42 ]. Acan et al [ 30 ] used grape pomace and achieved a TPC increment in chocolate spread formulations that ranged from 3.415 to 13.754 mg GAE/g chocolate.…”
Section: Resultsmentioning
confidence: 99%
“…Hardness of chocolate is a good parameter that points out proper control of temperature and stability of the fat crystal network formed during tempering process [24,25]. All treatments (VeC and SuSC) showed hardness values lower compared to the control samples (MiC and DaC) (Table 4).…”
Section: Texture Analysismentioning
confidence: 99%